2014
DOI: 10.1002/cncr.28900
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analyses of 6 different types of uterine smooth muscle tumors: Emphasis in atypical leiomyoma

Abstract: BACKGROUND: Uterine smooth muscle tumors (USMTs) constitute a group of histologic, genetic, and clinical heterogeneous tumors that include at least 6 major histologically defined tumor types: leiomyoma (ULM), mitotically active leiomyoma (MALM), cellular leiomyoma (CLM), atypical leiomyoma (ALM), uncertain malignant potential (STUMP), and leiomyosarcoma (LMS). Apart from ULM and LMS, the nature of these variants is not well defined. METHODS: A total of 167 cases of different USMT variants were collected, revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 48 publications
(58 reference statements)
6
87
2
4
Order By: Relevance
“…Our findings raise the intriguing possibility that leiomyomas with bizarre nuclei may be a precursor of leiomyosarcomas. Our data and findings from two previous studies 39,51 demonstrate that in contrast to leiomyomas, MED12 mutations in leiomyomas with bizarre nuclei and leiomyosarcomas do not occur frequently, and that these mutations may not act as 'driver' mutations in the development of leiomyomas with bizarre nuclei and leiomyosarcomas. To further explore the concept of tumor progression and to identify biomarkers to differentiate between diagnostically challenging uterine smooth muscle tumors, high-resolution molecular studies are needed to search for recurrent genetic changes in chromosome areas where overlap between leiomyomas, leiomyomas with bizarre nuclei, and leiomyosarcomas occur.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Our findings raise the intriguing possibility that leiomyomas with bizarre nuclei may be a precursor of leiomyosarcomas. Our data and findings from two previous studies 39,51 demonstrate that in contrast to leiomyomas, MED12 mutations in leiomyomas with bizarre nuclei and leiomyosarcomas do not occur frequently, and that these mutations may not act as 'driver' mutations in the development of leiomyomas with bizarre nuclei and leiomyosarcomas. To further explore the concept of tumor progression and to identify biomarkers to differentiate between diagnostically challenging uterine smooth muscle tumors, high-resolution molecular studies are needed to search for recurrent genetic changes in chromosome areas where overlap between leiomyomas, leiomyomas with bizarre nuclei, and leiomyosarcomas occur.…”
Section: Discussionsupporting
confidence: 68%
“…39,51 Overall, 25% of patients suffering from leiomyosarcomas in our study demonstrated a MED12 codon 44 mutations in the primary tumor. Surprisingly, in a patient (leiomyosarcoma1) with two subsequent leiomyosarcoma metastases that occurred 4 and 7 years after initial diagnosis MED12 mutation was no longer detectable in the metastases indicating that a tumor cell clone lacking MED12 mutation could have metastasized.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Various cell cycle regulatory proteins and tissue expression may have the potential for diagnostic utility [36,37]. Ki-67 is a non-histone nuclear protein only expressed in G1-M phases of the cell cycle, used as a marker of cellular proliferation.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Bcl-2 is a protein that regulates and prevents abnormal apoptotic cell death. This regulatory protein also promotes cellular replication by reducing the requirement for growth factors [36,[38][39][40].…”
Section: Immunohistochemistrymentioning
confidence: 99%